Genotoxic response of blood, gill and liver cells of Piaractus mesopotamicus after an acute exposure to a glyphosate-based herbicide - Leveroni, Flavia Antonela (2016)
The use of pesticides may affect the aquatic ecosystem. Through soil, these contaminants are drained into rivers. In South America, glyphosate-base herbicides, such as Roundup, are widely used in agricultural activities. In this work, the genotoxic effects of Roundup Full II® were evaluated in blood, gill and liver cells of Piaractus mesopotamicus, species of great ecologicaland commercial value in South America. Previously, the lethal concentration 50 (LC50) for 96 h of exposure was determined, with a theoretical value of 8.92 mg l?1. Genotoxic analysis in cells of the three tissues was performed by the comet, micronuclei (MN) and nuclear abnormalities (NA) assays after 96 h exposing fish to a sub-lethal concentration of Roundup Full II® (2.75 mg l?1).Comet assay results for the three tissues showed a significantly greater damage compared to the negative control and no statistical differences were observed between tissues responses. For MN and NA significantly higher frequencies were also demonstrated, indicating diverse kinds of damage like clastogenic events in the three tissues, with gills being the most sensitive one.